Therapeutic Strategies for High-Dose Vasopressor-Dependent Shock - Estevão Bassi; Marcelo Park; Luciano Cesar Pontes Azevedo (Critical Care Research and Practice)
There is no consensual definition of refractory shock. The use of more than 0.5 mcg/kg/min of norepinephrine or epinephrine to maintain target blood pressure is often used in clinical trials as a threshold. Nearly 6% of critically ill patients will develop refractory shock, which accounts for 18% of deaths in intensive care unit. Mortality rates are usually greater than 50%. The assessment of fluid responsiveness and cardiac function can help to guide therapy, and inotropes may be used if hypoperfusion signs persist after initial resuscitation. Arginine vasopressin is frequently used in refractory shock, although definite evidence to support this practice is still missing. Its associations with corticosteroids improved outcome in observational studies and are therefore promising alternatives. Other rescue therapies such as terlipressin, methylene blue, and high-volume isovolemic hemofiltration await more evidence before use in routine practice.